SMART WATER QUALITY MONITORING SYSTEM - Ryris Agatha Runggu Samosir; Friska Afrilia Hutasoit; Eka Dodi Suryanto; Dian Putra Saragi (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
Water quality is an important factor that affects human health, the environment, and various sectors of life. However, conventional water quality monitoring methods still have limitations, such as requiring a long time, high costs, and being unable to provide real-time data. This study aims to design a Smart Water Quality Monitoring System based on the ESP32 microcontroller capable of monitoring water quality automatically and continuously. The system uses several key parameters, namely pH, temperature, turbidity, and Total Dissolved Solids (TDS), which at the design stage are simulated using a potentiometer. Data from the sensors is processed by the ESP32 through an analogue-to-digital conversion process, then displayed in real-time on a 16×2 LCD and potentially sent to an Internet of Things (IoT) based platform. The design results indicate that the system is able to read and display data accurately according to input changes, and operates according to the designed algorithm. This system has advantages in terms of efficiency, ease of development, as well as multi-parameter monitoring capability. Thus, the designed system can serve as an alternative solution for more effective water quality monitoring and has the potential to be developed into an IoT-based remote monitoring system.